Crystal structure of 1,2-bis(6-bromo-3,4-dihydro-2H-benz[e][1,3]oxazin-3-yl)ethane: a bromine-containing bis-benzoxazine - Rivera, Augusto (Acta Crystallogr E Crystallogr Commun, 2016)
The title benzoxazine molecule, C(18)H(18)Br(2)N(2)O(2), was prepared by a Mannich-type reaction of 4-bromophenol with ethane-1,2-diamine and formaldehyde. The title compound crystallizes in the monoclinic space group C2/c with a centre of inversion located at the mid-point of the C—C bond of the central CH(2)CH(2) spacer. The oxazinic ring adopts a half-chair conformation. The structure is compared to those of other functionalized benzoxazines synthesized in our laboratory. In the crystal, weak C—H⋯Br and C—H⋯O hydrogen bonds stack the molecules along the b-axis direction.